Three-Dimensional Versus Two-Dimensional Echocardiographic Assessment of Functional Mitral Regurgitation Proximal Isovelocity Surface Area. (March 2015) - Ashikhmina, Elena; Shook, Douglas; Cobey, Fred; Bollen, Bruce; Fox, John; Liu, Xiaoxia; Worthington, Andrea; Song, Pingping; Shernan, Stanton
Abstract : BACKGROUND: The geometric shape of the mitral regurgitation (MR) proximal isovelocity surface area (PISA) is conventionally assumed to be a hemisphere (HS). However, in functional MR, PISA is frequently neither an HS nor a hemiellipse (HE) but is often asymmetric and crescent shaped. We used 3-dimensional transesophageal echocardiographic (3D TEE), full-volume data sets to directly measure the PISA and subsequently compared calculated values of effective regurgitant orifice area (EROA) with conventional 2D TEE techniques. EROA calculations from all PISA measurements were finally compared with the cross-sectional area at the vena contracta, a well-validated reference measure of the functional MR orifice area. METHODS: Twenty-four cardiac surgical patients with functional MR, who underwent routine intraoperative TEE examinations with a 3D matrix array probe (X7-2t; IE33; Philips Healthcare, Inc., Andover, MA) were retrospectively evaluated for MR severity using quantitative 2D and 3D TEE-derived techniques. Conventional 2D TEE methods were used to estimate PISA assuming an HS shape and an HE shape. In addition, direct measurement of the 3D PISA was obtained (QLab, Philips Healthcare, Inc.) from corresponding full-volume, color-flow Doppler data sets. EROAs calculated from HS- and HE-PISA techniques were compared with the same values obtained from 3D TEE PISAs. EROAs obtained from all 3 PISA techniques were subsequently compared with vena contracta area. RESULTS: Three-dimensional PISA was significantly larger than both HS-PISA and HE-PISA (mean ± SD: 4.65 ± 2.03 cm 2 vs 2.10 ± 1.58 cm 2 and 2.75 ± 1.42 cm 2 ; both P < 0.0001), respectively. HE-PISA was also larger than HS-PISA ( P = 0.042). In addition, 3D EROA was larger than both HS- and HE-acquired EROAs (mean ± SD: 0.44 ± 0.21 vs 0.19 ± 0.12 cm 2 and 0.26 ± 0.14; both P < 0.0001), respectively, while HE-EROA was larger than HS-EROA ( P = 0.024). Vena contracta area correlated well with 3D EROA (Spearman r = 0.865), HS-EROA (Spearman r = 0.820; P < 0.001) and HE-EROA (Spearman r = 0.819). However, the difference between vena contracta area and 3D EROA was significantly less than the differences between vena contracta area and either 2D HS- or 2D HE-EROA ( P < 0.0001). CONCLUSIONS: Quantitative assessment of functional MR severity by 3D TEE may be superior to 2D methods by permitting more direct measures of PISA. Two-dimensional TEE techniques for assessing functional MR severity that rely on an HS- or HE-PISA shape may underestimate the EROA due to geometric assumptions that do not account for asymmetry. Abstract : Published ahead of print August 27, 2014.